Studi Kasus Pengembangan Wirausaha Berbasis Teknologi (Technopreneurship) di Provinsi Gorontalo - Herwin Mopangga (Faculty of Economics and Business, University of Pasundan, 2015)
This study aims to describe the technology based entrepreneurial activity and non-technopreneurship, to elaborate the efforts to improve students’ and graduates’ interest to be the doers of technopreneurship, and to compile a document which will be the direction of development to lead technopreneurship in Gorontalo Province. This study used qualitative approach, the data collected by observation, interview, questionnaire and documentation, that located in 6 regencies/city in the Province of Gorontalo. This study concludes that, Low competitiveness of the product by small and medium business in Gorontallo Province is caused by limited technology mastery among entrepreneurs. If there are any technological innovations, it’s temporally only for exhibition purpose in regional and national scale, not to enhance the quality of products, diversification and efficiency in short-term, as well as sustainable increased of production, their income increased, and or business extension profit in the long-term. Technopreneurship development that partnership by State University of Gorontalo (UNG) and The Regency of North Gorontalo is the best practice to extend and strengthen technopreneurs in the region. Students interest in entrepreneurship can be increased by research based learning and student centered learning.